'Nothing happened': Legal implications of false denials among abused children. (18th September 2022) - Bücken, Charlotte A.; Otgaar, Henry; London, Kamala; Riesthuis, Paul; Battista, Fabiana; Mangiulli, Ivan
Abstract: People lie on a frequent basis. However, when a victim of maltreatment lies by denying the abuse, lies can become forensically relevant. We have reviewed the relevant literature on the prevalence and memory consequences of such false denials. The way forensic interviewers proceed in the face of denying children will be shaped by their beliefs about the frequency with which truly abused children deny abuse. We discuss that estimates of the prevalence of false denials among abused children vary but that such false denials do happen. When falsely denying children eventually come forward with their experiences, a second issue lingers: how valid are maltreated children's statements after a false denial? We review the literature indicating that false denials can negatively affect memory for the investigative interview during which the lie was told. Yet, memory for the denied experience itself seems to be mostly preserved, and some research even found potential protective effects of false denials. We conclude that denials should always be handled with care in the court room, since the ground truth usually is not known, but that statements should not be dismissed based solely on previous denials.